Nursing care for children with dengue hemorrhagic fever in fulfilling the needs of fluid and electrolytes at hative passo hospital : a case study - Bonara, Felisya; Fajar, Harianti (Innovative Approaches in Health Science Journal, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is a viral infectious disease transmitted through the bite of the Aedes aegypti mosquito and often attacks children. DHF can cause serious complications, such as dengue shock and bleeding, which require prompt treatment in hospital. Method: This study aims to provide nursing care for children with DHF, especially in meeting fluid and electrolyte needs. This case study uses a descriptive method with an interview approach, observation, physical examination, and nursing process. The study was conducted on one pediatric patient with one diagnosis at Hative Ambon Hospital for three days, namely on April 5-7, 2024. Results: The results of the case study showed that the priority diagnosis in the child was fluid volume deficiency related to lack of fluid intake, characterized by complaints of nausea, vomiting twice at home, headache, nosebleed once, red spots on the right hand, and low fluid intake while in the hospital. In addition, the patient looked weak, had dry lip mucosa, and had a fever with a temperature of 38.9°C. Conclusion: Providing fluids to children with DHF is an effective method to prevent dehydration and reduce the risk of further complications. Therefore, close monitoring of fluid and electrolyte balance is essential in nursing care of DHF patients.